Analysis of Patient Safety in TM/CAM Services, Women's Health and its Legal Perspective - Iwan Kusnawirawan; Koniasari; RM Alfian; Dini Nur Alpiah; Hafna Rosyita; Anindini Winda Amalia (Jurnal Health Sains, 2024)
Ensuring patient safety is a crucial aspect of healthcare including TM/CAM, particularly in the field of women's health. Healthcare providers must prioritize the safety of women during pregnancy and childbirth to prevent any harm or potential risks. This research used a traditional review, increasing the amount of literature that has been read and analyzed by the researcher. Normative-juridical principles in a prescriptive analytical manner with a statutory regulatory approach and the thinking method is deductive. General patient safety principles can be used in TM/CAM services by implementing the International Classification of Patient Safety (ICPS). Women are at risk due to their genital, hormonal, and pregnancy characteristics and may be affected by disease conditions acquired before or during pregnancy, and complications from physiological events at the end of pregnancy. Regulations on traditional health services and women's health care in Law No. 17 of 2023 and other regulations. This arrangement must guarantee safety, quality, and affordability. Patient safety is specifically regulated by Regulation of the Minister of Health of the Republic of Indonesia Number 11 of 2017 concerning Patient Safety. TM/CAM health services have developed in society and have to assess quality and safety standards, registration and accreditation have been established and TM/CAM health service practitioners, both those with formal and non-formal education, are required to have a competency certificate and Registration Certificate (STR). And Licenses (SIP) and Traditional Healers Registered Certificate (STPT).